Prediction of Hope and Morale During COVID-19 - Kimhi, Shaul; Eshel, Yohanan; Marciano, Hadas; Adini, Bruria (Frontiers in Psychology, 2021)
The current study uses a repeated measures design to compare two-time points across the COVID-19 pandemic. The first was conducted at the end of the "first wave" [T1] and the second was carried out on October 12-14 2020 (the last period of the second total general lockdown) in Israel. The participants (N=805) completed the same questionnaire at both time points. The study examined the predictions of hope and morale at T2 by psychological and demographic predictors at T1. Results indicated the following: (a) The three types of resilience (individual, community, and national) significantly and positively predicted hope and morale. (b) Well-being significantly and positively predicted hope and morale. (c) Younger age significantly and positively predicts higher hope, but not morale. (d) A higher level of religiosity significantly and positively predicts higher hope and morale. (e) More right-wing political attitudes significantly and positively predict higher hope, but not morale. (f) More economic difficulties due to the pandemic, significantly and negatively predict hope and morale. We concluded that hope and morale can serve as significant indicators of the population's ability to cope with the COVID-19 pandemic. Furthermore, they can serve as a "thermometer" for the general mood of the population and can be used by decision-makers to assess coping ability at varied stages of the pandemic.